Developmental mechanism of juvenile coccygeal fibrosis (so‐called coccygeal pad). Issue 10 (6th August 2013) - Hashimoto, Ichiro; Shono, Yoshitaka; Ishida, Soshi; Nakanishi, Hideki
Abstract Coccygeal pad is a nodular lesion in the sacrococcygeal area, typically involving a proliferation of collagen bundles. The etiology and optimal treatment remain unclear. We investigated the etiology using a systematic review of the available published work, two cases that we examined and treated, and measurements of body pressure in a sitting position in seven healthy volunteers. Forty‐two cases (34 male, eight female) from the published work were analyzed in terms of age at presentation and onset, clinical appearance, radiological findings, histopathological findings, treatment and etiology. Mean age at presentation was 18.6 years. The suspected age at onset in 30 cases (75%) ranged from elementary school to high school age. In terms of radiological findings, anterior dislocation of the coccyx was found in 79.5%. In terms of histopathological findings, marked thickening of the dermis due to the proliferation of collagen bundles was observed in all examined cases. No nodule recurrence was found after resection, even without surgical treatment of coccygeal bone prominence. Chronic stimulation on a sharply angulated sacrococcygeal joint was considered an etiologic factor in 79.4%. High pressure in the sacrococcygeal region in a relaxed sitting position on a hard school chair was shown in one of our cases and healthy children. This nodular lesion appears to represent a fibrous lesion related to chronic stimulation at school age. We propose a new name for this nodule, "juvenile coccygeal fibrosis", based on the pathological presentation and age predilection.